Green Supply Chain Management and Operational Performance: A Case Study at 5-Star Hotel in Bali - Astawa, I Ketut; Budarma, I Ketut; Widhari, Cokorda Istri Sri; Suardani, Anak Agung Putri (Technium Social Sciences Journal, 2020)
The purpose of this study is to examine the practices of environmentally friendly management carried out by the hospitality industry in greening the supply chain management and how these practices influence the operational performance. This is a quantitative and descriptive research with the case study approach used to validate the research framework. Data were purposively selected from 105 suppliers of food, beverage, chemicals, and Spa through observation, interviews, and questionnaires. The obtained data were analyzed using the Structural Equation Modeling and AMOS version 23, a data processing instrument. The results showed that there is a positive relationship between environmentally friendly supply chain practices and operational competence. The results also found that the adoption of environmentally friendly practices in supply chain management has a positive effect on operational performance. Green practices can be a key driver for raising environmental awareness for stakeholders and needs to be a priority in the tourism sector.